Impact of diet on inflammatory bowel disease risk: systematic review, meta-analyses and implications for preventionResearch in context - Antoine Meyer; Manasi Agrawal; Einat Savin-Shalom; Emily C.L. Wong; Carrie Levinson; Stephanie Gold; Neeraj Narula; Jean-Frédéric Colombel; Franck Carbonnel (EClinicalMedicine, 2025)
Summary: Background: Data on dietary risk factors for inflammatory bowel disease (IBD), while extensive, are inconsistent. Our aim was to systematically review and meta-analyze available data unraveling the relationship between diet and IBD subtypes, Crohn's disease (CD) and ulcerative colitis (UC). Methods: We conducted a systematic literature review following PRISMA guidelines, from inception to May 8 2025, using OVID Medline, Embase, and Scopus databases, to identify prospective cohorts of healthy participants, on the association between diet and the risk of CD or UC. Meta-analyses were performed using random-effects model, pooling hazard ratios (HRs) for each exposure category, relative to the lowest. Findings: Of 7916 studies identified by the search, 72 studies (65 in adults, 7 in children) met the inclusion criteria. The 65 adult cohort studies included 2.043.601 participants; 62.3% were women, the mean age at recruitment was 53.1 years and mean follow up was 12.8 years. Overall, 1902 participants developed CD and 4617 developed UC. Inflammatory diet (pooled aHR 1.63, 95% CI: 1.26, 2.11) and ultra-processed foods (pooled aHR 1.71, 95% CI: 1.36–2.14) were associated with an increased risk of CD. High fiber intake (pooled aHR 0.53, 95% CI: 0.41–0.70), Mediterranean diet (pooled aHR 0.59, 95% CI: 0.43–0.81), healthy diet (pooled aHR 0.70, 95% CI: 0.54–0.91), and unprocessed or minimally processed foods (pooled aHR 0.71, 95% CI: 0.53–0.94) were associated with a lower risk of CD. No consistent associations were found between individual foods or food patterns and the risk of UC. Interpretation: This study summarizes evidence on the link between specific dietary items or patterns and the risk of IBD. These data will help inform the design of prevention trials that include a dietary component as well as prevention strategies overall. Funding: This study received no funding